Peroxide values of Aglaia argentea Blume, A. silvestria (M. Roemer) Merr., dan A. tomentosa Teijsm. & Binn. - PRAPTIWI PRAPTIWI; MINDARTI HARAPINI; IDA ASTUTI (Society for Indonesian Biodiversity, 2006)
The objectives of this research were to determine the chemical components and the peroxide values of three Aglaia species (A. argentea Blume, A. silvestria (M. Roemer) Merr and A. tomentosa Teijsm & Binn). Phytochemical screening was done by Cuiley method, while peroxide values were determined by iodometri-titration on methanol, hexane, chloroform and ethyl acetate extracts. The result of phytochemical screening indicated that all of Aglaia species tested (three species) contained sterol and triterpenoids, base alkaloid, reduction sugar, and anthrasenoid while other components present only in one or two species of Aglaia. Peroxide values of the testedextracts were higher than that of vitamin E (40.996 mili-equivalent/1000 g samples) as a standard reductor, except the peroxide value of chloroform extract of A. tomentosa (41.078 milli-equivalent/ 1000 g sample). It can be concluded that A. tomentosa chloroform extract might had similar ability with vitamin E in preventing or delaying oxidation process. A. tomentosa chloroform extract acted as reductor.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Aglaia spp., chemical compounds, peroxide value.